SOCIO-PEDAGOGICAL NEED FOR THE DEVELOPMENT OF ARTISTIC AND CREATIVE SKILLS IN PUPILS (Scientific journal of the Fergana State University, 2023)
In this article, the need to develop artistic-creative skills in students, the main goal of developing artistic-creative skills of students is to form the young generation mature in all respects, well-rounded people necessary for the development of our society. comments are made.